2011
DOI: 10.1007/s00125-011-2314-2
|View full text |Cite
|
Sign up to set email alerts
|

Implication of dysregulation of the canonical wingless-type MMTV integration site (WNT) pathway in diabetic nephropathy

Abstract: Aims/hypothesis The wingless-type MMTV integration site (WNT) pathway mediates multiple physiological and pathological processes, such as inflammation, angiogenesis and fibrosis. The aim of this study was to investigate whether canonical WNT signalling plays a role in the pathogenesis of diabetic nephropathy. Methods Expression of WNT ligands and frizzled receptors in the canonical WNT pathway in the kidney was compared at the mRNA level using real-time RT-PCR between Akita mice, streptozotocin-induced diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
106
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 46 publications
3
106
0
Order By: Relevance
“…Recently, increasing evidence suggests that Wnt/ b-catenin plays a crucial role in the pathogenesis and progression of CKD. [21][22][23]34 As a key transcription regulator, b-catenin integrates major fibrogenic signal pathways and controls the transcription of numerous profibrotic genes. 31,35,36 In this study, we have uncovered that all components of the entire RAS, including AGT, renin, ACE, AT1, and AT2, are novel downstream targets of Wnt/b-catenin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, increasing evidence suggests that Wnt/ b-catenin plays a crucial role in the pathogenesis and progression of CKD. [21][22][23]34 As a key transcription regulator, b-catenin integrates major fibrogenic signal pathways and controls the transcription of numerous profibrotic genes. 31,35,36 In this study, we have uncovered that all components of the entire RAS, including AGT, renin, ACE, AT1, and AT2, are novel downstream targets of Wnt/b-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being relatively silent in normal adult kidneys, Wnt/b-catenin signaling is reactivated in a wide variety of CKDs, such as obstructive nephropathy, diabetic nephropathy, adriamycin (ADR) nephropathy, polycystic kidney disease, and chronic allograft nephropathy. [20][21][22][23][24] Accordingly, blockade of this signal cascade by an assortment of approaches is able to prevent kidney injury and ameliorate proteinuria and fibrotic lesions in animal models of CKD. 20,21,25 However, although both Wnt/b-catenin signaling and RAS are coincidently activated in diseased kidneys, whether they are directly related is completely unknown.…”
mentioning
confidence: 99%
“…11 Tzou et al reported that systemic injection of monoclonal antibody against Wnt receptor attenuates kidney damage in genetically insulin-deficient Akita mice. 12 However, not all of the experiments targeting Wnt-signaling inhibition were successful in treating DKD. An endogenous Wnt receptor antagonist DKK1 was thought to be a potential pharmacologic target for podocytopathy, but systemic DKK1 injection accelerated mesangial matrix accumulation in DKD.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] As a developmental signaling pathway, the Wnt/b-catenin system is essentially silenced in differentiated podocytes, but activated Wnt/b-catenin signaling has been found in various types of proteinuric kidney disease, [9][10][11] particularly in DKD. 10,12,13 Wnt/b-catenin is a key element of podocyte dysfunction by downregulating nephrin via a Snail-dependent mechanism. 10 Target inhibition of podocyte Wnt signaling does not alter kidney microstructure and function but prevents podocytopathy in doxorubicin-induced nephropathy.…”
mentioning
confidence: 99%
“…[11][12][13] Extensive studies have shown aberrant activation of b-catenin in glomerular podocytes in a range of animal models of proteinuric CKD and human biopsies from patients with various kidney disorders, such as FSGS, diabetic nephropathy, and IgA nephropathy. 7,14,15 Consistently, either genetic ablation of b-catenin in a podocyte-specific fashion or pharmacologic inhibition of b-catenin signaling protects mice against podocyte dysfunction and proteinuria after injury. 7,10,16 These studies suggest that dysregulated activation of b-catenin signaling could be a common mechanism leading to podocyte dysfunction and proteinuria.…”
mentioning
confidence: 89%